How Does Human Capital’s Impact to Cost of Financial Distress? - Widarwati, Estu; Haryono, Tulus (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: The important of human capital relation to firm financial distress still get limited attention, but there is some evidence that firm reduce the cost of human capital when its get a declining financial performance due to bankcruptcy. This study aims exploring the cost of financial distress determinant by human capital.Methodology: We use the data of manufacturing industry in Indonesia Stock Exchange (IDX) during 2011 – 2017. We use monetary approach for measuring human capital by income-base indicator i.e wage/salary and cost of financial distress measured by the difference of firm sales and industry sales. Furthermore, this study illustrates a tendency of cost of financial distress which controlled by firm size, firm age, and leverage. We analyze using static panel data and also doing robustness check as analysis completement. Results: The results find that human capital has positive significant impact to cost of financial distress and excess salary is a breakthrough of indicator for measuring human capital. Furthermore, the usage of firm size, firm age, and leverage as control variable, we find that larger and older firms able to more control their human capital against the cost of financial distress, thus, they can get the benefit of human capital increasing as their competitive strategy. Applications/Originality/Value: Based income indicator, exceess salary as measurement of human capital that built in this study supports the previous empirical studies in describing human capital’s impact to cost of financial distress. The results has practical implication that a firm should concern to welfare of employee as long as it does not exceed the firm’s revenue for avoiding firm’s bankruptcy. Furthermore,the goverment may should thinks about optimal standard of employee salary or wages in distressed firm according our finding of human capital role in firm costs.